Pernikahan bagi Penderita Gangguan Mental di Indonesia (Komparasi antara Perspektif Hukum Positif dan Prinsip Maslahah) - Pradikta, Hervin Yoki; Anggraini, Vira Mesi; Muhammad, Hasanuddin; Tunnur, Muti Aulia Zahro; Asnawi, Habib Shulton (Bulletin of Counseling and Psychotherapy, 2025)
This paper aims to examine the implementation of marriages carried out by people with mental disorders, namely one of the partners has psychoneurosis or neurosis disorders which are carried out at the Lubuk Batang Religious Affairs Office, Ogan Komering Ulu Regency and analyze them from the perspective of Islamic family law in Indonesia and maslahat. This type of research uses qualitative descriptive field research which describes or describes a situation, symptoms, or event systematically and factually regarding existing facts from primary data and secondary data. Observation, interviews and documentation obtained primary data. Meanwhile, secondary data comes from books, mass media and statutory regulations. As a result, when the wedding was held at Lubuk Batang Religious Affairs Office, people with mental disorders were conscious and healthy, this was because the mental disorders experienced by the groom in the couple were only temporary. As for the conditions and pillars of marriage that have been fulfilled and registered at the Lubuk Batang Religious Affairs Office, then from the perspektive of Islamic family law in Indonesia the marriage is valid. It is different if seen from the mashlahat persepktive, that it is better to avoid this marriage, because this mental disorder can recur at any time and affect family harmony.